3.7k views
4 votes
3x-1/5 = 2x+3/7

3x - 1 / 5 = 2x + 3 / 7 \\


User Dickeylth
by
4.5k points

2 Answers

4 votes

Answer:

123

Explanation:

User Emurano
by
5.2k points
3 votes


\large\underline{\sf{Solution-}}


\textsf{Given expression:}\\


\rm{ (3x - 1)/(5) = (2x + 3)/(7) } \\


\textsf{By, doing cross multiplication, we get}\\


\rm\longmapsto \:7(3x - 1) = 5(2x + 3) \\


\rm\longmapsto \:21x - 7 = 10x + 15 \\


\rm\longmapsto \:21x - 10x = 15 + 7 \\


\rm\longmapsto \:11x = 8 \\


\rm\therefore \:x = (8)/(11) . \\


\textsf{Hence, the value of x will be $(8)/(11)$ respectively.}\\

User Gowtham Balusamy
by
5.2k points